The correlation between visual acuity outcomes and optical coherence tomography parameters following surgery for diabetic epiretinal membrane and taut posterior hyaloid - Güngel H (Dove Medical Press, 2015)
Hülya Güngel, Zeynep Kayaarasi Öztürker, Sibel Zirtiloğlu, Kadir Eltutar Ophthalmology Department, Istanbul Research and Training Hospital, Istanbul, Turkey Purpose: To evaluate the relationship between visual outcomes and the determinants detected by spectral domain optical coherence tomography (OCT) in eyes with epiretinal membrane (ERM) and/or taut posterior hyaloid (TPH) that underwent pars plana vitrectomy (PPV). Materials and methods: A total of 30 participants with diabetic ERM and TPH were included in the study. All study participants underwent PPV. Preoperative and postoperative best corrected visual acuity (BCVA), peripapillary retinal nerve fiber layer (RNFL), macular RNFL, ganglion cell layer, inner plexiform layer, and ganglion cell complex thicknesses were measured in each participant. Linear regression analyses were performed to determine the association between the OCT parameters and the visual acuity measured at the time of the OCT measurement. Results: The postoperative BCVA logarithm of the minimum angle of resolution (logMAR) values were statistically higher than the preoperative values in the ERM group and TPH group (P=0.001 and P<0.001, respectively). The postoperative BCVA logMAR value was negatively correlated with average RNFL, inferior RNFL thicknesses, and image quality (P=0.002, P=0.004, and P=0.006, respectively). The preoperative and postoperative BCVA logMAR value difference was not correlated with age and all of the OCT parameters measured (P>0.05). Conclusion: This study shows that achievement of better peripapillary RNFL thickness results in better visual outcome after PPV and ERM/TPH removal. Keywords: diabetic epiretinal membrane, taut posterior hyaloid, retinal nerve fiber layer, ganglion cell complex, optical coherence tomography